THE IMPLEMENTATION OF PROBLEM-BASED LEARNING IN THE TEACHING OF READING AT HIGHER EDUCATION LEVEL - Astuti, Risa; Dewi, Sinta; Fujiarti, Hana Suci; Herawati, Dika Triya (IPI Garut Press, 2023)
Problem-Based Learning (PBL) is one of the teaching methods highly promoted in the status quo, especially in EFL classes. Regarding this, numerous studies indicate that PBL is effective in enhancing student learning performance, particularly in enhancing problem-solving abilities and self-efficacy learning. However, research on PBL's use in Indonesia, particularly in EFL reading classes, is still barely to be found. Hence, this study is aimed to investigate the implementation of PBL in EFL reading classes by means to investigate how the stages of PBL were implemented and to see what PBL principles have been achieved in the learning activity. This study is produced from qualitative research in the form of a case study, where observations were done during the learning process. The findings indicate that PBL is applicable to be implemented in higher education because the teacher’s actions cover all stages of PBL. However, there is still one principle that must be considered namely student collaboration. One of the expectations of teachers for students is that they can have critical thinking and be able to learn independently, therefore, this can be achieved by making PBL a learning method in the classroom.